Giant Axonal Neuropathy with CNS Involvement - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
Linkage and mutation analyses, MRI, EEG and EMG were performed in 6 patients with giant axonal neuropathy (GAN) from 3 consanguineous families examined at Hacettepe University, Ankara, Turkey, and centers in France.